THE CORRELATION BETWEEN STUDENTâ€™S MISBEHAVIOR WITH ENGLISH LEARNING ACHIEVEMENT OF THE EIGHT GRADE STUDENTS - Marlentera, Riris; Sudarsono, Sudarsono; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: This research was conducted to verify the previous research finding shown by Wini Miaryuna (2008). The number of Year-8 students of â€œSMP Negeri 16 Pontianakâ€ are 331 people. The sample is year-8 B, which consist of 32 students. This research using direct and indirect technique. To gather the data, checklist item, tally, daily score,mid score and final score are used in order to observe the data. The research found out that the typical misbehavior in the classroom was looking outside,beside, back and front. The average degree of studentsâ€™ achievement who doing misbehaviour in learning English is 5.7 and the average degree of studentsâ€™ achievement who do not doing misbehavior is 7.2. The degree of the correlation between studentsâ€™misbehavior and the studentsâ€™ English learning achievement is (-0.77) it is categorized strong correlation. This result showed that there is a negative correlation between students misbehavior and studentsâ€™ English learning achievement.Â Key words : Qualitative Research, Direct and Indirect Technique,Â Misbehavior Abstrak : Penelitian ini bertujuan membuktikan penelitian sebelum nya oleh Wini Miaryuna (2008). Total keseluruhan murid kelas 8 SMP N 16 Pontianak adalah 331 orang. Kelas yang di ambil untuk penelitian adalah kelas 8B,yang terdiri dari 32 siswa. Penelitian ini menggunakan teknik langsung dan tidak langsung. Untuk mengumpulkan data digunakanÂ tabel ceklis, nilai sehari-hari, nilai mid dan nilai ulangan akhir. Penelitian menemukan bahwa kelakuan buruk yang sering di perlihatkan murid adalah melihat keluar,kesamping ke depan dan belakang. Nilai rata- rata murid yang melakukan kebiasaan buruk adalah 5.7 dan nilai rata-rata murid yang tidak melakukan nya adalah 7.2. rata-rata dari korelasi antara kelakuan buruk murid dengan nilai mereka adalah (-0.77) yang dikategorikan sebagai korelasi kuat. Hasil ini menunjukkan bahwa ada hubungan antara kelakuan buruk murid saat dikelas dengan nilai bahasa inggris yang mereka capai.Â Kata Kunci : Penelitian Kualitative, Teknik Langsung dan Tidak Langsung, Kelakuan Buruk.Â